Problem-Based Workshop For Improving Product Diversification Of The Kolang-Kaling Process - Desnita Desnita; Iryani Iryani; Yenni Darvina (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
Tanah Datar Regency is known as one of the abundant fruit-producing areas of Kolang-Kaling. According to an interview by the PKM team with one of the heads of the women farmer groups, it was revealed that every week as many as 3 tons of Kolang-kaling fruit can be harvested. However, they only process 10% traditionally (boiled, peeled, and sold). The community does not have sufficient competence to apply technology in processing these plantation products into ready-to-eat food. As a result of the agreement with the two Cempaka Mekar and Teratai Women's Farmer Groups, also with the approval of the village head , a community partnership activity was agreed upon for these two farmer groups. With the aim of increasing the competence of women who are the target of activities in the application of technology for processing kolang-kaling fruit . Increasing competence is expected to have an impact on the welfare of the target community. In order to achieve the objectives, a problem-based workshop model was chosen, where the workshop activities were conducted based on partner problems, with an andragogical approach